2009
DOI: 10.1093/brain/awp241
|View full text |Cite
|
Sign up to set email alerts
|

Proximal dentatothalamocortical tract involvement in posterior fossa syndrome

Abstract: Posterior fossa syndrome is characterized by cerebellar dysfunction, oromotor/oculomotor apraxia, emotional lability and mutism in patients after infratentorial injury. The underlying neuroanatomical substrates of posterior fossa syndrome are unknown, but dentatothalamocortical tracts have been implicated. We used pre- and postoperative neuroimaging to investigate proximal dentatothalamocortical tract involvement in childhood embryonal brain tumour patients who developed posterior fossa syndrome following tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
134
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(147 citation statements)
references
References 38 publications
(62 reference statements)
9
134
1
3
Order By: Relevance
“…53,82 Miller et al, 63 using another perfusion imaging technique (dynamic susceptibility-weighted contrast-enhanced perfusion MRI), found that there is a strong (potentially predictive) relationship between bilateral damage to proximal efferent cerebellar pathways and the development of PFS. This finding was also supported by Kusano et al 57 and Morris et al, 65 the first who used diffuse-tensor imaging (DTI). Authors of a recent study from Berlin 91 also used DTI in a 3-T MRI suite and showed that volumes of frontocerebellar fibers had significantly diminished fractional anisotropy (FA) values in pediatric patients with CMS after surgery compared with patients without CMS and healthy peers.…”
Section: Pathophysiologysupporting
confidence: 63%
See 2 more Smart Citations
“…53,82 Miller et al, 63 using another perfusion imaging technique (dynamic susceptibility-weighted contrast-enhanced perfusion MRI), found that there is a strong (potentially predictive) relationship between bilateral damage to proximal efferent cerebellar pathways and the development of PFS. This finding was also supported by Kusano et al 57 and Morris et al, 65 the first who used diffuse-tensor imaging (DTI). Authors of a recent study from Berlin 91 also used DTI in a 3-T MRI suite and showed that volumes of frontocerebellar fibers had significantly diminished fractional anisotropy (FA) values in pediatric patients with CMS after surgery compared with patients without CMS and healthy peers.…”
Section: Pathophysiologysupporting
confidence: 63%
“…63 Multiple studies have supported the theory of cerebellocerebral diaschisis using different imaging techniques that revealed decreased blood flow, metabolic action, and function within supratentorial structures that play a crucial role in speech production, such as the thalami, inferior frontal gyrus, and temporal lobe. 26,34,63,65,83 In almost every case the abnormal findings returned to normal when mutism resolved.…”
Section: Pathophysiologymentioning
confidence: 92%
See 1 more Smart Citation
“…Damage to white matter connections within the cerebellar-thalamiccerebral network during surgical resection can cause posterior fossa syndrome, a clinical syndrome characterized by significant speech deficits including loss of expressive language (Morris et al 2009). The duration of speech difficulties associated with surgery can last from weeks to over a year with varying and nonlinear levels of language recovery.…”
Section: Posterior Fossa Syndromementioning
confidence: 99%
“…En el mutismo cerebeloso y en el síndrome de mutismo cerebeloso el sustrato anatómico más citado en la literatura tiene relación con el núcleo dentado y el tracto dento-rubro-talámico [17][18][19][20][21][22][23] .…”
Section: Introductionunclassified